Interpretation of the Yak Skin Single-Cell Transcriptome Landscape - Qingbo Zheng; Na Ye; Pengjia Bao; Tong Wang; Chaofan Ma; Min Chu; Xiaoyun Wu; Siyuan Kong; Xian Guo; Chunnian Liang; Heping Pan; Ping Yan (Animals, 2023)
The morphogenesis of hair follicle structure is accompanied by the differentiation of skin tissue. Mammalian coats are produced by hair follicles. The formation of hair follicles requires signal transmission between the epidermis and dermis. However, knowledge of the transcriptional regulatory mechanism is still lacking. We used single-cell RNA sequencing to obtain 26,573 single cells from the scapular skin of yaks at hair follicle telogen and anagen stages. With the help of known reference marker genes, 11 main cell types were identified. In addition, we further analyzed the DP cell and dermal fibroblast lineages, drew a single-cell map of the DP cell and dermal fibroblast lineages, and elaborated the key genes, signals, and functions involved in cell fate decision making. The results of this study provide a very valuable resource for the analysis of the heterogeneity of DP cells and dermal fibroblasts in the skin and provide a powerful theoretical reference for further exploring the diversity of hair follicle cell types and hair follicle morphogenesis.